2011
DOI: 10.1051/0004-6361/201117629
|View full text |Cite
|
Sign up to set email alerts
|

Seismic modelling of theβ Cephei star HD 180642 (V1449 Aquilae)

Abstract: Context. We present modelling of the β Cep star HD 180642 based on its observational properties deduced from CoRoT and groundbased photometry as well as from time-resolved spectroscopy. Aims. We investigate whether present-day state-of-the-art models are able to explain the full seismic behaviour of this star, which has extended observational constraints for this type of pulsator. Methods. We constructed a dedicated database of stellar models and their oscillation modes tuned to fit the dominant radial mode fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 44 publications
2
48
0
Order By: Relevance
“…The resulting periodogram from our SOFIN and FORS1 measurements displays three dominant peaks with the highest peak at f = 0.0720 d −1 corresponding to a period P = 13.893 d (Hubrig et al 2011d). This period was recently confirmed with seismic modeling based on CoRoT data and ground-based time-resolved spectroscopy by Aerts et al (2011), who also mention a somewhat high initial internal metallicity in their models, probably related to the presence of a magnetic field. The magnetic field geometry can likely be described by a centered dipole with a po- Fig.…”
Section: Magnetic Field Models For β Cephei and Spb Starssupporting
confidence: 52%
“…The resulting periodogram from our SOFIN and FORS1 measurements displays three dominant peaks with the highest peak at f = 0.0720 d −1 corresponding to a period P = 13.893 d (Hubrig et al 2011d). This period was recently confirmed with seismic modeling based on CoRoT data and ground-based time-resolved spectroscopy by Aerts et al (2011), who also mention a somewhat high initial internal metallicity in their models, probably related to the presence of a magnetic field. The magnetic field geometry can likely be described by a centered dipole with a po- Fig.…”
Section: Magnetic Field Models For β Cephei and Spb Starssupporting
confidence: 52%
“…Results from asteroseismic modelling of massive main-sequence pulsators are broadly consistent with overshoot of a few tenths of a pressure scale height, but show a range of best-fitting parameters from consistent with zero (e.g. Aerts et al 2011) to more than 40 per cent of a pressure scale height (e.g. Briquet et al 2007); further corroboration is found in isochrone fitting of open clusters (Brott et al 2011, and references therein).…”
Section: Overshoot Excitationmentioning
confidence: 57%
“…Given the fast rotation of a Be star, the observed frequency being twice as high as the highest one in the co-rotating frame of the star is less of a concern, as will be seen below. For the case of V1449 Aql this explanation is not unequivocally accepted; Aerts et al (2011) have suggested non-linear resonance arising from the interaction of a large number of other modes, while Degroote (2013) proposes that the dominant radial mode of V1449 Aql produces this signature through chaotic behavior. In any case, the similarity of the signature in the wavelet analysis remains striking, and the positive amplitude correlation between A 2 and A 3 could well be a clue towards the model of Aerts et al…”
Section: Outbursts and Pulsation Of Sthα166mentioning
confidence: 99%